Present and future of biblical studies : celebrating twenty-five years of Brill's Biblical interpretation - Liew, Tat-siong Benny. (Biblical Interpretation Series, 2018)
What is the current state of the field known as biblical studies? How will biblical studies continue to develop in this diverse, globalized, and digital age? In this book, a diverse group of scholars who are known for their innovative practice of biblical interpretation come together to celebrate the 25th anniversary of the critically acclaimed journal, Biblical Interpretation , by sharing their thoughts on and questions about the assumptions, practices, and parameters of biblical studies as well as their desires and fears about its disciplinary future. Covering a wide range of topics, geographical regions, resources, understandings, and viewpoints, this exceptional collection of essays will make you and help you rethink the conventions and convictions of biblical studies as an academic discipline.